Application of the factor method to the service life prediction of ETICS - Marques, Cristina; de Brito, Jorge; Silva, Ana (International Journal of Strategic Property Management, 2018)
This study intends to develop a methodology for service life prediction of ETICS (External Thermal Insulation Composite System), based on the factor method. The methodology adopted is based on data collected during visual inspections of buildings under current conditions of occupation and exposure, contemplating the degradation mechanisms and the characteristics of ETICS. This research can also provide a suitable tool to aid the planning, implementation and rational use of building management systems in several ways, namely: i) improvement of the materials’ performance, based on the optimization of maintenance actions, use of resources and maintenance costs; ii) selection of the best constructive solution, based on the knowledge of the evolution of degradation of ETICS, according to their characteristics; iii) analysis of the economic and environmental impacts of buildings during their life cycle, based on the knowledge of the number of replacements required during this period of time.